2020
DOI: 10.2478/forj-2020-0025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the European bark beetle Ips typographus on biochemical and growth properties of wood and needles in Siberian spruce Picea obovata

Abstract: European spruce bark beetle Ips typographus is an important driver of ecological processes in spruce stands, with severe effects on forestry economies. To prevent bark beetle outbreaks, early detection of infestations is a crucial step in forest management. It is expected that bark beetle infestation modifies biochemical composition of wood and needles, alters physiological responses in the early stage of infestation, which results in the reduction of tree growth and ultimately a tree death. Therefore, we stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…However, research on Siberian spruce (Picea obovata) infested with European bark beetle I. typographus showed that infested spruce wood had a lower tannin content. No effect of attack on resin formation was observed in this study [23]. Hood et al [24] noted, however, that many coniferous trees increase the amount of resin produced and change their composition after infestation with bark beetle [24,37,38].…”
Section: Structure Of Wood From Beetle-attacked Treescontrasting
confidence: 52%
See 1 more Smart Citation
“…However, research on Siberian spruce (Picea obovata) infested with European bark beetle I. typographus showed that infested spruce wood had a lower tannin content. No effect of attack on resin formation was observed in this study [23]. Hood et al [24] noted, however, that many coniferous trees increase the amount of resin produced and change their composition after infestation with bark beetle [24,37,38].…”
Section: Structure Of Wood From Beetle-attacked Treescontrasting
confidence: 52%
“…It is obvious that in the region where certain tree species are most affected by bark beetles, the properties of the wood of these tree species are investigated, and in other regions where bark beetles attack other tree species, the properties of those other tree species are investigated. For these reasons, research in Central and Eastern Europe deals mainly with spruce (Picea abies, Picea obovata Ledeb) [21][22][23] and in North America mainly pine (Pinus ponderosa Douglas ex C.Lawson, Pinus taeda L.) [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…3). For each species, the SLA was extracted from literature values: SLA LAGM = 120 cm 2 g −1 (Xian- Kui et al, 2015), which was also used for the closely related sister species LACA, SLA PIOB = 50 cm 2 g −1 (Konôpková et al, 2020), and SLA PISY = 50 cm 2 g −1 (extracted from the most recent source Błasiak et al, 2021, although other values are reported; 34 cm 2 g −1 in Reich et al, 1998, 40 cm 2 g −1 in Mencuccini and Bonosi, 2001). For PISI no source for SLA values was found and we assume it is similar to PISY: LA Tree i, Species j = BM dry needle SLA Species j /100,…”
Section: Addition Of Species and Estimating Leaf Area Index (Lai)mentioning
confidence: 99%